THE ROLE OF LOCUS OF CONTROL IN CONSUMER CREDIT DEBT BEHAVIOR DURING THE PANDEMIC COVID-19 BY USING RELIGIOSITY AS A MODERATING VARIABLE - Nurhidayat, Moch; Kusuma, Hadri; Hanafi, Syafiq Mahmadah (Jurnal Aplikasi Manajemen, 2023)
This study aims to empirically analyze the influence of locus of control variables on debtor behavior. In addition, this study also includes religiosity as a moderating variable to influence locus of control on the debtor behavior of consumption credit debtors during the Covid-19 pandemic. This research is quantitative, namely by conducting direct research on 155 respondent, objects to be analyzed using the statistical tool STATA version 14. The source of data in this study is primary data, namely, through surveys of respondents to obtain information in the form of respondents' opinions about debt management behavior during the pandemic Covid-19, the object of this research is Muslim respondents who have debt financial institutions, both Islamic/conventional and non-banking banks. The results showed that locus of control moderated by religiosity had a negative and significant effect on debt behavior so that the higher the locus of control moderated by religiosity, the lower the intensity of debt during the Covid-19 pandemic, religiosity had a positive and significant effect on debt repayment behavior where individuals who experience an increase in the locus of control moderated by religiosity will increasingly understand and carry out religious orders, namely to immediately pay off debts so that they do not become a burden in their lives. These findings indicate that the concept of locus of control can be used as an individual psychological factor to determine attitudes in making decisions on debt behavior, where individuals who have an increased locus of control are moderated by high religiosity, and these individuals have good self-control in managing debt.